H.C. Andersens livssyn og kristendomsforståelse - Pahuus, Mogens; Pahuus, Mogens (Dansk Teologisk Tidsskrift, 2018)
This article is not a complete assessment of Kaj Mogensen’s voluminous doctoral dissertation. Instead, it focuses on two elements in Hans Christian Andersen’s understanding of life and conception of Christianity: 1) God as loving providence, and 2) the importance of the freedom, endeavours and formation of the human being. It is argued that there is a range of difficulties in the first element – both in Hans Christian Andersen’s thinking and in Kaj Mogensen’s own corresponding approach – that are not sufficiently discussed in the dissertation. It is also argued that Mogensen to some degree underestimates the second element in Andersen’s novels, poems and fairy-tales.